AIR POLLUTION WITH SULFUR OXIDES FROM INDUSTRY IN SOUTH-WESTERN AND SOUTH-EASTERN REGIONS OF BULGARIA: AIR POLLUTION WITH SULFUR OXIDES FROM INDUSTRY IN SOUTH-WESTERN AND SOUTH-EASTERN REGIONS OF BULGARIA - Todorova, Mariana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Restructuring of industrial production and the concrete environmental measures such as fuel switching facilities and replacement of process equipment in the energy-intensive industries, the installation of new or increased efficiency of existing treatment facilities have caused emissions into the atmosphere to decrease significantly. However, the concentration of sulfur oxides in air showed no significant improvement, despite reduced emissions.